2006
DOI: 10.1111/j.1365-2141.2006.06140.x
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical stem cell transplantation for children with acute leukaemia

Abstract: 9/l. Relapse (14 patients) and adenoviral (six patients) or fungal infections (four patients) were the major causes of death. Haploidentical stem cell transplantation can produce medium term disease-free survival in a proportion of children with high-risk or relapsed acute leukaemia. None of the nine patients with acute myeloid leukaemia not in remission have survived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 16 publications
4
49
1
2
Order By: Relevance
“…41 Recent series of nsTCD haploidentical HSCT have reported significant rates of late TRM in both children and adults, predominantly from delayed T-cell immune reconstitution and viral infections, resulting in overall TRM of 40% to 60%. 4,40,42,43 In contrast we saw no significant morbidity or mortality related to viral infection and no TRM beyond 6 months post-BMT. Although the incidence of CMV reactivation in our study was lower than that in recent reports of nsTCD haploidentical HSCT, many such studies used detection techniques with greater sensitivity.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…41 Recent series of nsTCD haploidentical HSCT have reported significant rates of late TRM in both children and adults, predominantly from delayed T-cell immune reconstitution and viral infections, resulting in overall TRM of 40% to 60%. 4,40,42,43 In contrast we saw no significant morbidity or mortality related to viral infection and no TRM beyond 6 months post-BMT. Although the incidence of CMV reactivation in our study was lower than that in recent reports of nsTCD haploidentical HSCT, many such studies used detection techniques with greater sensitivity.…”
Section: Discussionmentioning
confidence: 42%
“…Our strategy resulted in a low cumulative incidence of cGVHD (8%) comparable to nsTCD haploidentical HSCT, 4,40 and surviving patients were therefore free of cGVHD-associated morbidity and immunosuppression. In contrast, recent studies of T-replete G-CSFstimulated haploidentical BMT have reported up to 70% cGVHD (and nearly 50% extensive cGVHD) in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five patients died of relapse. Among eight patients who received chemotherapy or radiation therapy followed by modified DLI, seven (four with haematological relapse and three with extramedullary relapse) were alive at a median follow-up of 15 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months after the diagnosis of relapse. Among the 12 AML patients who had haematological relapses, 2 received chemotherapy, followed by modified DLI, but they died of relapse at 4 and 6 months after their relapses, respectively.…”
Section: Engraftment Of Patients With Hid Donorsmentioning
confidence: 99%
“…For HSCT with related HIDs, extensive T-cell depletion or CD34 þ cell selection in vitro, mega-dose infusion and other supportive techniques have increased the rate of engraftment, reduced TRM and improved survival. 6,7 The latest reports of T-cell depletion HSCT from HID parental donors showed improved outcomes in the recent treatment era, with 5-year OS rates of 65% and 74% for very high-risk ALL and AML patients, respectively. 8 At our institution, promising results with unmanipulated, HID HSCT have been achieved in adult patients without ex vivo T-cell depletion, demonstrating outcomes similar to those with MSDs and well-matched unrelated HSCT.…”
Section: Introductionmentioning
confidence: 99%